Management of Marfan Syndrome during pregnancy: A real world experience from a Joint Cardiac Obstetric Service. (15th September 2017) - Lim, Joanna C.E.-S.; Cauldwell, Matthew; Patel, Roshni R.; Uebing, Anselm; Curry, Ruth A.; Johnson, Mark R.; Gatzoulis, Michael A.; Swan, Lorna
Abstract: Background: Pregnancy in Marfan Syndrome (MFS) is associated with increased maternal risk of cardiovascular events. Given the maternal and genetic risks, pre-conception counselling is essential to facilitate informed choices. Multidisciplinary antenatal care with regular imaging is mandatory and best delivered through a Joint Cardiac Obstetric Service (JCOS). The aim of this study was to compare the care delivered in a JCOS against recognised international standards (European Society of Cardiology (ESC)). Methods: Pregnancies in women with MFS from 2005 to 2015 were identified from our institutional database. Patient records were reviewed and practice assessed against pre-determined standards based on ESC guidelines. Results: There were 23 pregnancies in 15 women with MFS. 13/23 (57%) occurred in women with aortic dilatation at baseline. There were 3 important maternal cardiac events (type A dissection; deterioration in left ventricular function; significant left ventricular and progressive aortic dilatation). Four women did not have access to expert pre-conception counselling. These women were all referred to the JCOS late in established pregnancy. Imaging was often delayed and only 7/23 cases (30%) met the standard for minimum frequency of echocardiographic surveillance. Only 12/23 (52%) had pre-conception imaging of the whole aorta with CT/MRI. Distal aortic dilatation was identified in 7/23 cases but none of these underwent further MRI evaluation during pregnancy. Conclusion: Despite having a dedicated JCOS, our data show that facilitating complete obstetric and cardiac care for this group remains challenging. Education of local care providers and timely referral for expert pre-conception counselling in a JCOS are key.